Enhancing comfort of resident physicians treating adults with intellectual and developmental disabilities by facilitating meaningful interactions - Sanders, Jessica Solomon; Williams, Kathryn; Thompson, Darcy; Shapiro, Hannah F. (Frontiers in Medicine, 2024)
Background Many physicians feel uncomfortable caring for patients with intellectual and developmental disabilities (IDD). While some residency training programs include lecture content on IDD, few provide structured experiences with individuals with IDD. One strategy for improving comfort is “contact theory:” increasing interactions with “dissimilar” people can lead to decreased negative attitudes toward that population. Objective Evaluate the impact of an interactive session on resident physicians’ comfort with adults with IDD. Methods Small groups of resident physicians and artists with IDD collaborated on art projects during the noon conference. A prospective pre-post-intervention survey, including the validated Interaction with Disabled Persons Scale (IDP), evaluated residents’ comfort with patients with IDD before and after the session. Results 53 residents completed both pre- and post-conference surveys. Mean IDP scores decreased from 78.7 (10.9) to 75.8 (9.5; p < 0.01), indicating decreasing discomfort. The mean level of comfort interacting with individuals with IDD increased from uncomfortable 3.6 (1.2), before the intervention, to comfortable 4.4 (1.2) after the intervention (p = <0.01). The mean level of comfort treating individuals with IDD increased from uncomfortable 3.5 (1.1) to comfortable 4.1 (1.3) after the intervention (p < 0.01). Discussion Providing resident physicians with real-life connections with people with IDD was associated with increased comfort. If statistically significant improvements occurred after one session, future studies should evaluate if additional experiences with people with IDD could have more substantial, lasting impacts on future doctors’ comfort with and willingness to care for patients with IDD.